A vidéki városi agglomerációk fejlődési pályája - Hajnalka Lőcsei (Hungarian Academy of Sciences, Institute of Economics, 2004)
– Urban regions are the most favoured geographical knots of the economic power and growth, and of the Hungarian social transformation as well. In 2003 the Hungarian Central Statistical Office surveyed the processes of agglomeration and modified the previous demarcation of the clusters of settlements. The provincial urban agglomerations were studied in this spatial context (because of their specific character, Budapest and the area of lake Balaton were not included). They were compared, classified and categorized on the basis of income, local tax and employment indices in the period of 1990.2001. On the one hand these urban regions were described in general according to their level and course of development, on the other hand the inner inequalities were analysed as a stressed point of view. This latter one is intent on establishing the results of suburbanisation, whether it made the urban regions homogeneous or divided. We are also analysing influencing factors of inequalities such as size, regional position or level of development.
Keywords: 330; Stadtentwicklung; Regionales Cluster; Suburbanisierung; Ländlicher Raum; Ungarn